LANGUAGE POLICIES OF TURKIC REPUBLICS AFTER THEIR INDEPENDENCE AND THE WORKS WITH TURKEY ON COMMON LANGUAGE AND COMMON ALPHABET - Abdıeva, Rakhat (Ahmet BURAN, 2017)
After the collapse of Soviet Union, in the first years of independence in different fields there have been many changes which bear the traces of Soviet Union, especially of Russia, in Turkic Republics. Among those changes the most important ones are the changes such as the adoption of the constitutions of the republics, the identification of the flags and arcs, and the determination of their own currencies. Moreover, in that period, the topics like state language, language policy, a common written language and common alphabet with other Turkic Republics have come to the fore. This study will analyze the works of common language and alphabet planned to be created among Turkic Republics, the language policies applied in these republics and their current situation.

Sovyetler Birliğinin dağılmasından sonra Türk Cumhuriyetlerinde bağımsızlığın ilk yıllarında Sovyetler Birliği, özellikle de Rusya’nın izlerini taşıyan birçok alanda değişiklik yapılmıştır. Bu değişikliklerin başında cumhuriyetlerin kendi anayasalarının kabul edilmesi, bayrak ve armalarının tespit edilmesi, kendi para birimlerinin belirlenmesi gibi değişiklikler gelmektedir. Ayrıca bu dönemde devlet dili, dil politikası, diğer Türk Cumhuriyetleri ile ortak bir yazı dili ve ortak alfabe konuları gündeme gelmiştir. Çalışmada Türk Cumhuriyetleri arasında oluşturulması planlanan ortak dil ve ortak alfabe çalışmaları, cumhuriyetlerin uyguladığı dil politikaları ve bu çalışmalarda günümüzde gelinen nokta değerlendirilmeye çalışılmıştır.
BAĞIMSIZLIKLARINI KAZANDIKTAN SONRA TÜRK CUMHURİYETLERİNİN DİL POLİTİKALARI VE TÜRKİYE İLE ORTAK DİL VE ORTAK ALFABE ÇALIŞMALARI
Keywords: Linguistics; Dilbilim